"Not See, Not Hear, Not Speak": Preschoolers Think They Cannot Perceive or Address Others Without Reciprocity. Issue 1 (1st January 2017) - Moll, Henrike; Khalulyan, Allie
Abstract : A curious phenomenon in early social-cognitive development has been identified: Preschoolers deny that they can see others who cannot also see them (Russell, Gee, & Bullard, 2012). The exclusive focus on vision has suggested that this effect is limited to gaze, but children's negations might reflect a broader phenomenon that extends to vocal communication. In Experiment 1 ( N  = 24), 3- to 4-year-olds were asked if they could see an agent whose eyes were covered, hear an agent whose ears were covered, and speak to an agent whose mouth was covered. In all cases, negative responses were more frequent than in a control condition in which the facial area was unoccluded. Experiment 2 ( N  = 24) provided evidence that children's negations did not result from a misunderstanding of the questions. The findings suggest that young children apply a principle of reciprocal relatedness that is not limited to gaze.